FlyTED: the Drosophila Testis Gene Expression Database. - Zhao, J; Klyne, G; Benson, E; Gudmannsdottir, E; White-Cooper, H; Shotton, D (2010)
FlyTED, the Drosophila Testis Gene Expression Database, is a biological research database for gene expression images from the testis of the fruit fly Drosophila melanogaster. It currently contains 2762 mRNA in situ hybridization images and ancillary metadata revealing the patterns of gene expression of 817 Drosophila genes in testes of wild type flies and of seven meiotic arrest mutant strains in which spermatogenesis is defective. This database has been built by adapting a widely used digital library repository software system, EPrints (http://eprints.org/software/), and provides both web-based search and browse interfaces, and programmatic access via an SQL dump, OAI-PMH and SPARQL. FlyTED is available at http://www.fly-ted.org/.